Modelling The Factors That Predict Fake News Sharing Behaviour Among Social Media Users In Nigeria: The Moderating Role Of Fake News Awareness - Destiny, Apuke Oberiri (2022)
Despite the growing scholarship on fake news on social media, there have been limited studies that have focused on understanding fake news sharing behaviour, especially in developing countries. To fill this gap, this study attempts to realise why people share fake news and how to prevent its spread via public awareness in the Nigerian context. Thus, the study developed a comprehensive model that encompassed various possible factors to explain why Nigerians tend to share fake news online. The study identified several factors that were derived from earlier investigations on news sharing and relevant theories to include user (individual) motivational factors (uses and gratifications theory) online environmental factor (social capital theory) medium factor (uses and gratifications theory); and content/message factor (diffusion of innovation theory), to develop a comprehensive predictive model of fake news sharing. The study further extended to test the role of fake news awareness (moderating variable) in reducing fake news dissemination as well as used news sharing behaviour construct as a mediating variable between individual motivational factor, online environmental factor medium factor, content/message factor and fake news sharing behaviour. Thus, the study is divided into five-fold statistical testing, which is the test of direct effects, mediating effects, and moderations. Using snowball sampling, the study recruited a total of 664 social media users across Nigerian geopolitical zones. The data was obtained from the respondents via an online survey (survey monkey) and later analysed using PLS path modelling.